DEVELOPMENT OF FRACTIONAL BOARD MEDIA ON THE UNDERSTANDING OF THE CONCEPT OF CLASS II STUDENTS - Fahira Mahmuda; Ima Muyawati (Universitas Majalengka, 2024)
The purpose of this study is to develop a learning media for Fractional Boards and test how effective it is in increasing the understanding of the concept of fractions among grade II students at SDN Susukan 09 Pagi. Fractional board media is a concrete media developed in development research with R&D methods and using 4D development models. With the existence of learning media as a means of learning and increasing students' understanding of concepts. Understanding the concept is very important, especially in fractional material, because students often think of fractions only as symbols that must be manipulated, not as whole whole whole numbers. Briefly, the results of the study show that this fractional board is considered very feasible with a validation percentage from media experts 96.67%, material experts 95.83%, teacher trials 88.00%, student trials 91.56%, average scores of pre-test students 66.66, and post-test students 88.00. Thus, this fractional board learning media is considered feasible to be used in the teaching and learning process for Grade II Elementary School students to improve their understanding of mathematical concepts.